Spontaneous Lumbar Artery Rupture: Diagnostic and Therapeutic Challenges in Anticoagulated Patients - Mesa, Cindy; Perafan, Luis; Bustamante, Luis; Urrego, Jonathan; Montenegro , Andrés (Journal of Endovascular Resuscitation and Trauma Management, 2025)
Spontaneous rupture of the lumbar artery is a rare and potentially life-threatening complication, particularly in anticoagulated patients. Its diagnosis is challenging due to nonspecific symptoms and rapid progression. We present the case of a 78-year-old woman, without prior arterial disease, who developed atrial fibrillation during hospitalization and was started on enoxaparin (1 mg/kg every 12 hours). She subsequently developed hemodynamic instability, prompting urgent imaging. An initial ultrasound showed a right flank hematoma, and a computed tomography angiogram confirmed a retroperitoneal hematoma due to lumbar artery rupture. The patient received aggressive resuscitation and hemodynamic support, followed by successful catheter embolization, which stabilized her condition. This case highlights the importance of considering spontaneous lumbar artery rupture in anticoagulated patients presenting with unexplained hemodynamic instability. Early diagnosis and timely endovascular intervention can be life-saving and improve outcomes.